Proveniência e idade do metamorfismo das rochas da faixa Brasilia, na região de tapira (SW de Minas Gerais) - Da Silva, Carlos Humberto; Simões, Luiz Sergio Amarante [UNESP]; Krymsky, Robert; Macambira, Moacyr José Buenano (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2006)
The Brasilia Fold Thrust Belt at Tapira area (SW of Minas Gerais State, Brazil) has four different litho-tectonic domains imbricated by thrust faults with vergency to the São Francisco Craton. Sm/Nd isotopic studies were undertaken and the results show different model and metamorphic ages for the thrust sheets. Rocks from the lower thrust sheet yield a metamorphic age of 543 Ma while the upper thrust sheet has a metamorphic age of 581 Ma. The TDM model ages are similar for both thrust sheets, between 1.7 and 2.2 Ga. Because of their lithologic characteristics, the thrust sheets are interpreted as having been deposited in a distal continental platform environment, their main source being Paleoproterozoic rocks of the São Francisco Craton. The upper thrust sheet rocks presents a metamorphism age of 612 Ma and a bimodal distribution of TDM model ages between 1.3 and 1.9 - 2.0 Ga, respectively. The lithologic and isotopic characteristics of this thrust sheet the rocks are interpreted as a result of deposition on a continental slope or oceanic floor environment, with mixed contributions from Paleo - and Mesoproterozoic rocks of the São Francisco Craton. In spite of the small number of analyzed samples and the uncertainties inherent to the Sm/Nd method the metamorphisms are not considered to be synchronous in the different thrust sheets. This is to be expected in a thrust belt system, in which the more metamorphosed thrust sheets are juxtaposed to less metamorphosed ones.
Origin and metamorphic ages of the rocks of the Brazilia Fold Thrust Belt in the Tapira area (SW of Minas Gerais)
Keywords: Araxá Group; Brasília Belt; Canastra Group; Sm/Nd ages; evolution; lithology; metamorphic rock; Proterozoic; thrust fault; Brazil; Minas Gerais; Sao Francisco Craton; South America; Canastra